Аналіз маркетингових заходів торговельної мережі методами Text Mining - Грибков, Сергій Віталійович; Ханбабаєв, Р. Р.; Харкянен, Олена Валеріївна (My University, 2020)
У статті досліджено та проаналізовано методи Data Mining для формування й оцінки маркетингових заходів торговельної мережі. Особливу увагу приділено аналізу технології Text Mining. Це інструментарій, розроблений на основі базових технологій Data Mining у поєднанні зі статистичним і лінгвістичним аналізами, методами штучного інтелекту, який дає змогу здійснювати пошук тенденцій, шаблонів і взаємозв'язків у неструктурованих текстах для прийняття управлінських рішень.Наведено приклад реалізації моделей Text Mining у компонентному програмному пакеті Orange з використанням Twitter API. Робочі моделі для практичної реалізації завдань торговельної мережі сформовані на основі набору віджетів Orange. Результат дослідження візуалізовано у вигляді діаграм і хмар зі слів, які зручно переглядати й аналізувати.

The article researches and analyzes the methods of Data Mining for the formation and evaluation of marketing activities of the trade network. Special attention is paid to the analysis of Text Mining technology. This is a toolkit developed on the basis of basic Data Mining technologies in combination with statistical and linguistic analysis, methods of artificial intelligence, which allows you to search for trends, patterns and relationships in unstructured texts for management decisions. Data mining is a process of discovering patterns in large data sets involving methods at the intersection of machine learning, statistics, and database systems. Building a strategy of trade network development requires the study of the information field in which the company operates, an objective assessment of the activities, comparing bonus programs of its own network and competitors. Despite the large number of information sources for their rapid processing and classification is indispensable use of software products implementing Text Mining technology. Text mining similar to text analytics, is the process of deriving high-quality information from text. Written resources may include websites, books, emails, reviews, and articles. High-quality information is typically obtained by devising patterns and trends by means such as statistical pattern learning. Thus, in order to evaluate the success of the marketing activities of the trade network, information support is offered using the methods of text tone and search for anomalies Text Mining technology based on data from the social network Twitter. An example of Text Mining models implementation in Orange component software package using Twitter API is given. Working models for the practical implementation of the trade network tasks are formed on the basis of a set of Orange widgets. The result is visualized in the form of diagrams and clouds of words, which are easy to view and analyze.
Keywords: кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; інтелектуальний аналіз даних; соціальні мережі; Data Mining; Text Mining; social networks